Interview: Advancing personalized medicine to improve health outcomes. (May 2009) - Issa, Amalia
Amalia Issa is the founding Director of the Program in Personalized Medicine and is currently Associate Professor of Pharmacological and Pharmaceutical Sciences at the University of Houston (TX, USA). She has developed an unique area of translational research focused on pharmacogenomics and personalized medicine and how applications of personalized medicine will be translated and integrated into healthcare delivery and health systems. Issa was among the first scientists to publish papers on translational research and health policy issues related to personalized medicine and she is internationally recognized in this field.